The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3389/fmicb.2013.00014
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Dynamics as a Structuring Factor for Microbial Carbon Utilization in a Subtropical Coastal Lagoon

Abstract: Laguna de Rocha belongs to a series of shallow coastal lagoons located along South America. It is periodically connected to the sea through a sand bar, exhibiting a hydrological cycle where physicochemical and biological gradients are rapidly established and destroyed. Its most frequent state is the separation of a Northern zone with low salinity, high turbidity and nutrient load, and extensive macrophyte growth, and a Southern zone with higher salinity and light penetration, and low nutrient content and macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 63 publications
4
9
1
Order By: Relevance
“…However, in this study this may not have been the case. As it has been previously described for this ecosystem, nutrients and DOM concentrations are usually higher in the North zone, although DOM is not always in a bioavailable form (Conde et al, 2002;Piccini et al, 2009;Alonso et al, 2013). In the present study, the North zone also showed a higher concentration of inorganic nitrogen forms and a high C:N ratio, suggesting that although nitrogen was available a great portion of DOM carbon could have not been available for bacterial growth, since it was mainly plant or macrophytederived (allochtonous origin).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…However, in this study this may not have been the case. As it has been previously described for this ecosystem, nutrients and DOM concentrations are usually higher in the North zone, although DOM is not always in a bioavailable form (Conde et al, 2002;Piccini et al, 2009;Alonso et al, 2013). In the present study, the North zone also showed a higher concentration of inorganic nitrogen forms and a high C:N ratio, suggesting that although nitrogen was available a great portion of DOM carbon could have not been available for bacterial growth, since it was mainly plant or macrophytederived (allochtonous origin).…”
Section: Discussionsupporting
confidence: 63%
“…Each microcosm was amended with ( 15 NH 4 ) 2 SO 4 (99% at., Aldrich, St. Louis, MO, USA)) at a final concentration of 50 nmol L -1 , which was used in order to be close to 10% of ambient concentration and avoid over enrichment (Conde et al, 2000;Aubriot et al, 2005). Incubations were run at the in situ temperature (15°C) in a circulating water bath under PAR intensity of 689 µmol m -2 s -1 and subsamples were taken at 0, 0.5, 2 and 4 h. The short incubation times were chosen according to previous studies on site (Piccini et al, 2009;Alonso et al, 2013) considering the bacterial activity and its dynamics as well as to prevent the effect of confinement on bacterial growth as it has been reported (Fergusson et al, 1984;Fuchs et al, 2000). Water samples from LW treatment were size-fractioned post-incubation using 1.2 µm glass fiber filters (GF/C Whatman Inc., Florham Park, NJ, USA) to retain most of the phytoplankton community (phytoplankton-enriched fraction, PHYTO) Vidal et al, 2007); the resulting filtrate was passed through 0.5 µm glass fiber filters (GE Water & Process Technologies, Boulder, CO, USA) to get the bacterioplankton community (bacteria-enriched fraction, BACT).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, little is known on how photoaltered CDOM from different macrophyte species affects the bacterial community. Alonso et al (2013) recently showed that the addition of allochthonous carbon sources induces pronounced shifts in the bacterial assemblage of a shallow coastal lagoon, while the amendment of nutrients such as nitrogen (N) or phosphorus (P) does not have a significant effect on it. These results suggest that bacterioplankton growth in this type of aquatic ecosystem would be predominantly limited by carbon and that this limitation would be more or less intense depending on the hydrology of the system (Alonso et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Alonso et al (2013) recently showed that the addition of allochthonous carbon sources induces pronounced shifts in the bacterial assemblage of a shallow coastal lagoon, while the amendment of nutrients such as nitrogen (N) or phosphorus (P) does not have a significant effect on it. These results suggest that bacterioplankton growth in this type of aquatic ecosystem would be predominantly limited by carbon and that this limitation would be more or less intense depending on the hydrology of the system (Alonso et al, 2013). The reason for this limitation is probably that during some phases of the lagoon hydrology, the main source of organic carbon for bacteria is macrophytes-derived DOM, which due to their chemical composition cannot be readily incorporated by bacteria for growth.…”
Section: Introductionmentioning
confidence: 99%